Fashion Style Milenial Perspektif Feminisme Mary Wollstonecraft - Yahdiani Hanani; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss millennial fashion style from the feminist perspective of Mary Wollstonecraft. The research method used is a qualitative type through literature study. The results and discussion of this study is that there is Mary Wollstonecraft's theory of feminism in millennial fashion style. This millennial fashion style is often seen as a blend of traditional and modern styles, with an emphasis on comfort and a unique and individual style. Millennial fashion style is seen as a reflection of the values and culture of the millennial generation, including concern for the environment and social issues. This study concludes that from Mary Wollstonecraft's feminist perspective, millennial fashion that fights for the value of gender equality uniquely respects individuals and will be seen as a positive fashion style. Fashion that offers women the freedom to express themselves individually and fight for their rights as independent individuals and will be considered as fashion in accordance with Mary Wollstonecraft's feminist principles. Conversely, if millennial fashion is seen as a tool to perpetuate gender stereotype discrimination against women, then this fashion is not in accordance with Mary Wollstonecraft's feminist principles.